2002
DOI: 10.1124/dmd.30.11.1214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Reduced Elimination Clearance of Benzylpenicillin from Cerebrospinal Fluid in Rats with Intracisternal Administration of Lipopolysaccharide

Abstract: ABSTRACT:The mechanism responsible for the reduced clearance of benzylpenicillin (BPC) from the cerebrospinal fluid (CSF) was investigated in rats that received an intracisternal administration of lipopolysaccharide (LPS). BPC was intraventricularly injected and its elimination from the CSF studied. During the inflammation created by the LPS administration to the cisterna magna, the clearance of BPC and taurine from the CSF was significantly reduced but reverted to the control level when N-nitro-L-arginine, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The BCSFB is involved in the continuous removal of prostaglandin E2 from the CSF, keeping low the intracerebral levels of this proinflammatory mediator [156]. A downregulation of prostaglandin E2 efflux transporters occurs in the models of bacterial meningitis and viral infection, and may exacerbate the effects of neuroinflammation [57,67]. Chronic moderate hyperbilirubinemia Fig.…”
Section: Pro-oxidant Speciesmentioning
confidence: 99%
“…The BCSFB is involved in the continuous removal of prostaglandin E2 from the CSF, keeping low the intracerebral levels of this proinflammatory mediator [156]. A downregulation of prostaglandin E2 efflux transporters occurs in the models of bacterial meningitis and viral infection, and may exacerbate the effects of neuroinflammation [57,67]. Chronic moderate hyperbilirubinemia Fig.…”
Section: Pro-oxidant Speciesmentioning
confidence: 99%
“…For example, the active clearance of organic anions in the choroid plexus was strongly impaired by exposure to inflammatory stimuli (33). It has also been reported that the uptake of benzylpenicillin in choroid plexus was reduced and CSF levels was increased in an experimental meningitis model (33-35). These changes can disrupt both the diffusion clearance and active clearance of drugs at BCSFB in our model.…”
Section: Discussionmentioning
confidence: 87%
“…Reduced uptake of benzylpenicillin by the choroid plexus has been reported in rats that received intracisternal LPS, an experimental model of bacterial meningitis (Han et al . ). As rat OAT3 is the transporter responsible for the uptake of benzylpenicillin (Nagata et al .…”
Section: Discussionmentioning
confidence: 97%
“…Each point represents the mean ± SEM (n = 6-10). been reported in rats that received intracisternal LPS, an experimental model of bacterial meningitis (Han et al 2002). As rat OAT3 is the transporter responsible for the uptake of benzylpenicillin (Nagata et al 2002) and PGE 2 in the choroid plexus, the OAT3-mediated PGE 2 clearance from the CSF would be reduced as a result of inflammation, leading to the continuous accumulation of PGE 2 in the CSF.…”
Section: Discussionmentioning
confidence: 99%